Effectiveness of Intradialytic Exercise on Muscle Strength and Fatigue Score in Chronic Kidney Failure (CKF) Patients in the Grandmed Hemodialysis Room - Purba, Anita Gandaria; Sagala, Deddy Sepadha Putra; Ali Sabela Hasibuan; Yuni Suharnida Lubis (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2024)
Chronic kidney failure is a progressive and irreversible kidney dysfunction in which the body's ability to maintain metabolism, fluid and electrolyte balance is disrupted, resulting in uremia or azotemia. Hemodialysis is a form of treatment for patients with chronic kidney failure, in which the patient's blood is diverted out of the body through a dialyzer, which occurs through diffusion and ultrafiltration, after which the blood is returned to the patient's body. Several methods to maintain muscle strength and reduce fatigue scores, namely intradialytic exercise is an exercise program developed that can increase muscle strength, muscle endurance and physical activity. The general objective of this study was to determine the effectiveness of intradialytic exercise involvement interventions on muscle strength and fatigue scores in hemodialysis patients at GrandMed Lubuk Pakam Hospital. This research method is a quantitative study, using a quasy experiment with a one group pre-test post-test design. The population in this study were all patients with Chronic Kidney Failure who were recorded at the Medical Records Hospital Grandmed Lubuk Pakam from October 2021 to December 2022. With inclusion criteria: respondents experienced movement disorders, muscle cramps, and weakness. The number of samples was 22 respondents. The sampling technique used in this research is non-probability sampling, namely purposive sampling. The statistical test used is the Wilcoxon test. The Wilcoxon test results obtained significant results from the intradialytic exercise technique on muscle strength and fatigue scores with a p value of 0.00 each. So that it can be concluded that there is an effect of giving good intradialytic exercise interventions on muscle strength & fatigue scores in chronic kidney failure patients undergoing hemodialysis